Pendampingan Pengembangan Kurikulum Model Taba Berbasis Pemikiran Ki Hadjar Dewantara Dalam Mengatasi Problematika Kurikulum Merdeka Di SMK - Isa Ansori; Bachtiar Sjaiful Bachri; Lamijan Hadi Susarno (Pusmedia Group Indonesia, 2026)
Vocational education curricula in Indonesia continue to face complex structural challenges, including excessive administrative orientation, rigid centralized approaches, and limited opportunities for teachers to act as curriculum developers who are responsive to industry demands and students’ characteristics. This community service program aimed to assist teachers at SMKN 6 Surabaya in improving their curriculum design competencies through the implementation of the Taba Model based on the educational philosophy of Ki Hadjar Dewantara. The program involved 48 teachers from eight vocational departments and was conducted over two weeks using a participatory mentoring approach through theoretical workshops, Focus Group Discussions (FGDs), collaborative teaching material development practices, peer review sessions, and reflective activities. The results showed a significant paradigm shift from teachers functioning merely as curriculum implementers toward becoming independent grassroots curriculum developers. In addition, teachers demonstrated improved abilities in designing teaching modules and instructional materials aligned with workplace needs, as well as integrating the values of Ki Hadjar Dewantara—Among System, freedom of learning, and the principles of Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, and Tut Wuri Handayani—into curriculum practices. All eight vocational departments successfully produced teaching modules and instructional materials with an average quality score of 85/100. In conclusion, the collaborative mentoring program based on the Taba Model effectively transformed teachers’ perspectives and produced relevant, humanistic, and industry-oriented instructional materials.